1977
DOI: 10.1029/gl004i005p00195
|View full text |Cite
|
Sign up to set email alerts
|

Heavy ion circulation in the Earth's magnetosphere

Abstract: We propose a mechanism whereby singly charged heavy ions from the plasmasphere are convected intermittently to the dayside magnetopause, accelerated there, swept into the distant tail lobes and boundary layer and convected earthward in the plasma sheet to re‐enter the inner magnetosphere. The outer region of the plasmasphere is known to be stripped off during periods of enhancement of the convection electric field. These cold plasmaspheric ions drift toward the dayside magnetopause where they may become acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…There is plenty of evidence that outer plasmasphere material can convect to the magnetopause. During geomagnetic storms, cold plasmaspheric ions are commonly seen immediately adjacent to the magnetosheath and/or low-latitude boundary layer (LLBL) in the noon and mid-afternoon local time sector [Freeman, 1969;Borovsky et al, 1996;Elphic et al, 1996, and references therein]. Even at non-storm times, cold ions are caught up in the LLBL convection [Gosling et al, 1990], and are accelerated during transmission through or reflection from the magnetopause [Fuselier et al, 1991 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is plenty of evidence that outer plasmasphere material can convect to the magnetopause. During geomagnetic storms, cold plasmaspheric ions are commonly seen immediately adjacent to the magnetosheath and/or low-latitude boundary layer (LLBL) in the noon and mid-afternoon local time sector [Freeman, 1969;Borovsky et al, 1996;Elphic et al, 1996, and references therein]. Even at non-storm times, cold ions are caught up in the LLBL convection [Gosling et al, 1990], and are accelerated during transmission through or reflection from the magnetopause [Fuselier et al, 1991 ].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Observations have increasingly revealed that enhanced magnetospheric circulation, driven by the solar wind and its linked interplanetary magnetic field, results in the transport of the outer layers of the plasmasphere toward the dayside subsolar magnetopause, creating ''plasmaspheric plumes'' [Grebowsky, 1970;Chappell et al, 1970Chappell et al, , 1971Freeman et al, 1977;Sandel et al, 2001;Goldstein et al, 2004;Chandler and Moore, 2003;Moore, 2004, 2006]. The plasmasphere is supplied by a light ion outflow analogous to the polar wind, commonly known as ''refilling flows'' because they flow on closed low-latitude flux tubes and build up substantial densities over several days.…”
Section: Introductionmentioning
confidence: 99%
“…After reaching the dayside magnetopause, plasmaspheric material can then be transported on reconnected field lines over the polar cap and down the magnetotail (Su et al, , 2001a. It is unclear what portion of the formerly plasmaspheric material is drained down the magnetotail and lost to the solar wind as opposed to entering the plasma sheet and being eventually recirculated into the inner magnetosphere (Freeman et al, 1977;Elphic et al, 1997;Borovsky et al, 1997). Plasma sheet ion density and composition measurements (e.g., Lennartsson and Shelley, 1986) suggest that although some fraction of this eroded plasmaspheric material may join the plasma sheet, the vast majority of it is likely lost to the solar wind before the field line reconnects in the distant magnetotail.…”
Section: Introductionmentioning
confidence: 99%